The Impact of Engineering Design-Based STEM Education on Students' Attitudes Toward STEM and Problem-Solving Skills - Gafur Şimşek; Ayşegül Üldeş; Yasemin Taş; Önder Şimşek (Journal of Science Learning, 2023)
The impact of engineering design-based STEM education on 9th-grade high school students' attitudes toward STEM and their problem-solving skills was examined in this study. The subject of factors affecting the heat conduction rate in solids was taught using STEM education. In an experimental design with one group pre-test and post-test, students completed a STEM attitude scale and problem-solving inventory before and after the treatment. According to the paired samples t-test findings, students' attitudes toward mathematics, engineering, and 21st-century skills increased significantly, whereas their attitudes toward science and problem-solving did not change. The eta-squared effect size suggests a high level of change for other dependent variables but only a moderate change for problem-solving skills. In light of the findings, several recommendations about incorporating engineering design-based STEM education have been suggested.